Sirolimus and everolimus in kidney transplantation. Issue 10 (October 2015) - Moes, Dirk Jan A.R.; Guchelaar, Henk-Jan; de Fijter, Johan W.
Highlights mTOR inhibitors have proven their efficacy and offer renal and antiviral benefits. Sirolimus and everolimus differ mainly in pharmacokinetic characteristics. Novel approaches of monitoring mTOR inhibitors based therapy are under development. Pharmacogenetics of mTOR inhibitors should be expanded to pharmacodynamics.